Language, identity, and ideology: High achieving scholarship women - Dominguez-Whitehead, Yasmine; Liccardo, Sabrina; Botsis, Hannah (South African Journal of Higher Education, 2016)
This paper addresses the linguistic identities of high achieving women who are participants in a prestigious scholarship programme. We examine how high achieving women negotiate and construct their linguistic identities within the context of the university’s Anglicised institutional culture and against the backdrop of South Africa’s multilingual society. Individual and focus group interviews were examined by employing an experience-centred and culturally orientated approach to narrative (Squire 2008). Our examination reveals that language is both an academic and social intermediary of experience at university, and that language functions as both an identity marker and as an ideology that permeates the university and wider society. How participants transgress and maintain their linguistic identities, as well as how they subvert, and align with, the dominant university ideology is discussed.